Short-Term Resistance Training Improves Cardiac Autonomic Modulation and Blood Pressure in Hypertensive Older Women: A Randomized Controlled Trial. Issue 1 (January 2020) - Oliveira-Dantas, Filipe F.; Brasileiro-Santos, Maria do Socorro; Thomas, Scott G.; Silva, Alexandre S.; Silva, Douglas C.; Browne, Rodrigo A.V.; Farias-Junior, Luiz F.; Costa, Eduardo C.; Santos, Amilton da Cruz
Abstract : Abstract: Oliveira-Dantas, FF, Brasileiro-Santos, MdS, Thomas, SG, Silva, AS, Silva, DC, Browne, RAV, Farias-Junior, LF, Costa, EC, and Santos, AdC. Short-term resistance training improves cardiac autonomic modulation and blood pressure in hypertensive older women: a randomized controlled trial. J Strength Cond Res 34(1): 37–45, 2020—This randomized controlled trial investigated the efficacy of short-term resistance training (RT) on cardiac autonomic modulation and peripheral hemodynamic parameters in hypertensive older women. Twenty-five hypertensive older women who were insufficiently active (64.7 ± 4.7 years) participated in this study. Subjects were randomly allocated to a 10-week RT program (2 d·wk −1 in the first 5 weeks; 3 d·wk −1 in the last 5 weeks) or a nonexercise control group. Linear reverse periodization was used for the RT program. Cardiac autonomic modulation, mean blood pressure (MBP), peripheral vascular resistance (PVR), and resting heart rate (RHR) were measured before and after 10 weeks. The RT group reduced cardiac sympathetic modulation (0V%; B = −6.6; 95% confidence interval [CI]: −12.9 to −0.2; p = 0.045; Cohen's d = 0.88) and showed a trend for increased parasympathetic modulation (2V%; B = 12.5; 95% CI: 0–25; p = 0.050; Cohen's d = 0.87) compared with the control group. The RT group reduced MBP (B = −8.5 mm Hg; 95% CI: −13.6 to −3.4; p = 0.001; Cohen's d = 1.27), PVR (B = −14.1 units; 95% CI: −19.9 to −8.4; p < 0.001; Cohen's d = 1.86), and RHR (B = −8.8 b·min −1 ; 95% CI: −14.3 to −3.3; p = 0.002; Cohen's d = 1.20) compared with the control group. In the RT group, the changes in 2V% patterns and low-frequency components showed a correlation with changes in MBP ( r = −0.60; p = 0.032) and RHR ( r = 0.75; p = 0.0003). In conclusion, 10 weeks of RT improved cardiac autonomic modulation and reduced MBP and PVR in hypertensive older women. These results reinforce the importance of RT for this population.